Patient Satisfaction with Intensive Care Services in the Medical ICU of Shree Birendra Hospital - A Descriptive Cross-sectional Study - Adhikari, Anita; Pokharel, Sunita; Amatya, Bishow Ram; Panta, Chiranjibi; Mulepati, Sumitra (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Intensive care unit is a highly sophisticated hospital area which is specifically designed, well equipped and dedicated for the management of critically ill patients. Patient satisfaction is their perception of care and quality of service which is dependent upon their needs and expectations. Thus, the objective of the study is to find out the patients’ satisfaction with intensive care unit care. Methods: This is a descriptive cross-sectional study conducted among the patients transferred out to different wards and discharged from medical ICU of Shree Birendra Hospital, Kathmandu, Nepal. A total of 145 patients were selected by using non-probability purposive sampling methods. Structured questionnaire in Nepali version was used to interview the patients. Data was analyzed by using descriptive statistics and inferential statistics in SPSS version 25. Results: More than half (53.1%) patients were male, with mean age of 59.4 years. Around 50% of patients were from the 60 - 80 years age group. On average, patients stayed in the hospital for about six days. Most of them (84.1%) were from army families, and 15.9% were active-duty soldiers. Among 145 patients, 109 (75.2%) had high level of satisfaction and 36 (24.8%) had low level of satisfaction. There was no association between demographics variables and satisfaction level. Conclusions: Most of the patients were related to military personnel with the most common reason for ICU admission being respiratory problems. Overall, most patients were satisfied with the care they received in the ICU.